Hip flexor length as a predictor of hip extensor weakness in recreational runners - Correia, Gerard Jose (My University, 2014)
Janda described lower crossed syndrome (LCS) as tightness of the thoracolumbar extensors along with tightness of the iliopsoas and rectus femoris muscles. This is crossed with weakness of the deep abdominal muscles and weakness of the gluteus maximus and gluteus medius muscles. Janda identified the LCS as common postural changes involving the hip flexor extensor mechanism. Janda’s LCS provides the framework that can account for the postural observations and changes noted around hip musculature. Although this framework has been routinely applied and cited in an attempt to understand faulty posture better, the complexities of his theory still remain conceptual. Limited evidence seems to be available that has specifically shown how an antagonistic muscle group (hip flexor and hip extensor) can directly affect each other sufficiently to disrupt normal muscle functioning. Methodology: This study’s aim was to determine whether the length of the hip flexor can be used to predict hip extensor weakness. Thirty two recreational runners were recruited to participate in this study. The modified Thomas test was performed on each participant to measure hip flexion length along with an isokinetic hip extension test that measured hip extensor strength. The correlational study was undertaken to compare the hip flexor length to ipsilateral hip extensor strength. 4 Results: The results did uncover variability in male versus female hip function in the population of recreational runners. In addition, a strong negative relationship between two-joint hip flexor length and hip extensor strength was found in the female group. Conclusion: Two-joint hip flexor length may be a predictor of hip extensor strength in female recreational runners.